The Australian Digital Market: Opportunities and Challenges - Madden, Gary; Ahmad, Hasnat (Edward Elgar, 2015)
While Australia was a latecomer in introducing ADSL, most Internet subscribers quickly migrated from dial-up service, with 96.4% broadband connections at June 2012. The national commitment to the universal provision of high-speed broadband (speeds to 100 Mbps) is a key Government objective and is implemented through the National Broadband Network (NBN). Although in an early-deployment phase the NBN is enabling, for example, selected IT companies to receive 40 Mbps upload speeds that can support many costumers at affordable prices. Furthermore, technological advance has facilitated the development and delivery of a wide range of consumer data services and applications. In particular, broadband is commonly used for shopping, search, gaming, media entertainment and social networking. Consumers are purchasing goods and services online, with shoppers increasingly using smartphones for this purpose. Also, the use of tablets and Internet-enabled mobile phones is popular and is facilitating mobile commerce and fundamentally changing the mode of business-customer interaction. This changing consumer behaviour is reshaping retail landscapes, stimulating retailers to develop digital strategies to meet customer expectations. For businesses, e-commerce provides opportunities to reduce costs and enhance sales. Indeed $189 billion of online orders were received during 2010/11. Importantly, 43% businesses report an online presence via a Website, eBay store or social media page.This digital revolution is also encouraging online service delivery and engagement by the Government. The Government recognises that online service delivery is both convenient and efficient. Examples of these developments include the Digital Local Government Program that helps communities in NBN-deployment areas to develop planning applications, consultations and reports. Another program, Tell US Once, is an ongoing initiative that aims to ensure customers only provide information once rather than repeatedly to several agencies. This chapter presents a snapshot of an increasingly dynamic Australian digital market and discusses evolving opportunities and challenges offered to consumers, businesses and the government.